Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fimmu.2022.834757
|View full text |Cite
|
Sign up to set email alerts
|

Durable Expansion of TCR-δ Meta-Clonotypes After BCG Revaccination in Humans

Abstract: Mycobacterium bovis bacille Calmette-Guérin (BCG) has been used for 100 years and prevents disseminated tuberculosis and death in young children. However, it shows only partial efficacy against pulmonary tuberculosis (TB) in adults, so new vaccines are urgently needed. The protective efficacy of BCG depends on T cells, which are typically activated by pathogen-derived protein antigens that bind to highly polymorphic major histocompatibility complex (MHC) molecules. Some T cells recognize non-protein antigens v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…gd T cells have been broadly described as innate-like, but recent studies have revealed phenotypic and functional heterogeneity both between and within Vd1 and Vd2 responses including subpopulations displaying characteristics aligned with adaptive immunity (15)(16)(17)(18)(19). Either Vd1 or Vd2 T cells transiently expand in response to infection or malignancy.…”
mentioning
confidence: 99%
“…gd T cells have been broadly described as innate-like, but recent studies have revealed phenotypic and functional heterogeneity both between and within Vd1 and Vd2 responses including subpopulations displaying characteristics aligned with adaptive immunity (15)(16)(17)(18)(19). Either Vd1 or Vd2 T cells transiently expand in response to infection or malignancy.…”
mentioning
confidence: 99%
“…The absence of clonotypic expansions after infant BCG vaccination could be due to a lack of depth of analysis necessary to identify the relevant clonotypes, lack of full maturation of gd T cells in infants with poor expansion capacity after BCG vaccination, and/or the relative insufficiency of the g 9 d 2 T cell subset present in infancy compared with other subsets of gd T cells. Seshadri (19) et al used peripheral blood mononuclear cells (PBMC) derived from a Phase I study of South African adults in which samples were archived at baseline, 3 weeks, and 52 weeks post-BCG revaccination. They found TRDV*02+CACDTLLGDTRTDKLIF to be a metaclonotype associated with BCG vaccination, enriched post-BCG in 9 of 17 samples and persisting for 1 year.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, BCG-trained monocytes boost responses to different exposures through non-antigen-specific mechanisms, including increased cytokine and chemokine release and the support of memory adaptive responses [ 253 ]. Recent findings also suggest that BCG induces sustained changes in the T cell repertoire, potentially contributing to long-term protection [ 254 ]. Applying trained immunity to enhance specific HIV responses across multiple clades is an intriguing concept, with trained monocytes initiating the response; this is followed by effective adaptive cytotoxic responses against conserved HIV regions.…”
Section: Vaccine Induced Correlates Of Hiv In Humans and Nhpmentioning
confidence: 99%